2019
DOI: 10.1093/jee/toz268
|View full text |Cite
|
Sign up to set email alerts
|

Drones: Innovative Technology for Use in Precision Pest Management

Abstract: Arthropod pest outbreaks are unpredictable and not uniformly distributed within fields. Early outbreak detection and treatment application are inherent to effective pest management, allowing management decisions to be implemented before pests are well-established and crop losses accrue. Pest monitoring is time-consuming and may be hampered by lack of reliable or cost-effective sampling techniques. Thus, we argue that an important research challenge associated with enhanced sustainability of pest management in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(108 citation statements)
references
References 251 publications
0
73
0
4
Order By: Relevance
“…In this sense, several studies are related to the use of A4.0 technologies, such as sensing and actuation drones to identify and control pests in crops [20], sensors and Internet of Things (IoT) for water management [21], agricultural decision support systems [22], proximal images and machine learning (ML) to identify nutritional deficiencies in crops [23], among others. These technologies assist in data collect, information analysis, diagnostics and formulation of strategies for the agricultural sector [24].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, several studies are related to the use of A4.0 technologies, such as sensing and actuation drones to identify and control pests in crops [20], sensors and Internet of Things (IoT) for water management [21], agricultural decision support systems [22], proximal images and machine learning (ML) to identify nutritional deficiencies in crops [23], among others. These technologies assist in data collect, information analysis, diagnostics and formulation of strategies for the agricultural sector [24].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to neonicotinoids can occur via different pathways, including pollen, nectar, guttation fluids, soil, air, and noncrop vegetation (Roubos et al 2014, Mogren and Lundgren 2016, Calvo-Agudo et al 2019, and sublethal and lethal effects have been reported for pollinators (Blacquière et al 2012, Whitehorn et al 2012, Rundlöf et al 2015 and natural enemies, potentially undermining vital pollination and biological control services (Pisa et al 2015, Calvo-Agudo et al 2019. High levels of exposure were reported for different species of farmland birds (Humann-Guilleminot et al 2019), and sublethal impacts have been reported for large vertebrates, such as deer (Gibbons et al 2015, Berheim et al 2019. Residues of neonicotinoids have been found in honey all over the world, at potentially harmful concentrations for nectar-feeding insects in 48% of the samples (Mitchell et al 2017).…”
Section: Crisis and Disastermentioning
confidence: 99%
“…At present, a suite of alternative pest control methods are available, including economic damage threshold levels, microbial control agents, semiochemical methods, and biological control (Barzman et al 2015, Furlan and Kreutzweiser 2015, Furlan et al 2018, Jactel et al 2019, even though not all alternatives rank well in terms of efficacy, applicability, durability, and practicability (Jactel et al 2019). The recent emergence of "disruptive innovations" (Juma 2016), such as robotic weeders, farm-level sensing, weed-suppressing intercrops, or drone-based https://www.ecologyandsociety.org/vol25/iss3/art26/ delivery of natural enemies carries ample promise (Lamichhane et al 2016, Iost Filho et al 2020. Political initiatives are needed to overcome eventual economic constraints, ease farmer transitions, and influence the trade-off between costs and benefits of insecticide use (Clark and Tilman 2017, Milner and Boyd 2017, van Lenteren et al 2018.…”
Section: Escape and Reorganization Of Neonicotinoid Usementioning
confidence: 99%
“…In addition to plant characterization, the aerial imagery provides useful information for field-risk management. For example, pale leaf color (indicating nitrogen deficiency), leaf rolling (as drought responses), weed growth, disease infection, and lodging [44,45] can be monitored and the necessary actions undertaken. Furthermore, high performance cameras capturing multispectral and thermal imagery can determine the stress tolerance-indicators under high temperature, drought, or salinity conditions ( Figure 1c).…”
Section: Pre-screening For Accelerating Pgr Researchmentioning
confidence: 99%